2019
DOI: 10.1186/s12889-019-6476-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of intentional drowning mortality: a total population retrospective cohort study in Australia, 2006–2014

Abstract: Background While a downward trend in unintentional drowning deaths in Australia has been observed, little is known about intentional drowning mortality. Limited information on intentional drowning death impedes the planning, implementation, and evaluation of prevention strategies. This study aims to describe rates of intentional fatal drowning in Australia and compare these to other categories of drowning. Methods Data were sourced from the Australian Bureau of Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 75 publications
2
25
0
Order By: Relevance
“…46 Data time periods ranged from 1987 to 30 June 2019, with one study comparing by remoteness in Western Australia (WA) from 1953-1962 to 1983-1992. 37 Studies varied in their use of classification systems for remoteness with 20 studies using standard classification systems, 3,12,[18][19][20][21][22][23][24][25][26][27]30,[38][39][40][41][42][43]46 four studies modifying existing standard classification systems 16,29,44,45 and eight studies using their own classification system (Table S2). 28,31-37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Data time periods ranged from 1987 to 30 June 2019, with one study comparing by remoteness in Western Australia (WA) from 1953-1962 to 1983-1992. 37 Studies varied in their use of classification systems for remoteness with 20 studies using standard classification systems, 3,12,[18][19][20][21][22][23][24][25][26][27]30,[38][39][40][41][42][43]46 four studies modifying existing standard classification systems 16,29,44,45 and eight studies using their own classification system (Table S2). 28,31-37…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies (65.6%) reported epidemiological data by remoteness. Eighteen studies included fatal data 3,12,16,[18][19][20][22][23][24][25][26][27]29,32,34,37,38,44 while five included non-fatal data. 3,16,20,27,44 Three studies included grouped data on both fatal and nonfatal drowning.…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition to unintentional external cause of drowning codes, watercraft and flood-related drowning, and intentional self-harm by drowning codes were also included. Studies have suggested to include these later codes (drowning from watercraft, flood related and intentional self-harm) to obtain more representative magnitude of fatal drowning 28 29. Intentional drownings particularly suicides are culturally stigmatised in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, future research should focus on the intent for drowning in Africa, which would help to inform policies and prevention interventions. A recent article on intentional drowning reported an increasing rate of intentional drowning and proposed a multidisciplinary collaboration public health and other services including mental health, education and drowning prevention organisations to prevent intentional drowning [71].…”
Section: Discussionmentioning
confidence: 99%